Bearing Capacity and Deformation of Timber Pile-Raft Foundation on Soft Soil Deposits - Muhammad Yunus; Risman Firman (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
A pile-raft foundation is a type of foundation that combines two different types of foundations, a raft base and a pile foundation. These raft bases are one of the most practical economic solutions for buildings because both the support capacity of the raft and the support capability of the pile both work. The paper presents results of the test bearing capacity of piled-raft foundations made from timber in the laboratory and analyzes numerically the deformations that occur in piled raft foundations made of timber. The results of the loading test on the Bakau piled raft foundations in the laboratory obtained the maximum load that can be held by the foundation before experiencing a failure of 85.00 kN with a deformation value of 21.50 mm. Whereas from the load vs. deformation curve, the ultimate bearing capacity is obtained by the Bakau piled raft foundations at 59.00 kN with an ultimate settlement of 6.00 mm. From the results of the validation between the loading test results of the foundation model in the laboratory and the results of numerical analysis, which compared the results of laboratory tests and the results of plaque analysis, the soil with reinforcement of Timber piled raft foundations gave results that were not much different.